Health Perceptions of Police Officers in Korea: An Investigative Study - Dongmin Lee; Seohyun Park; Byeong Kwan Woo; Yeon-Cheol Park; Jion Kim (MEDrang Inc., 2024)
Background: Police officers are an occupational group with a high risk of developing musculoskeletal, cardiovascular, and mental diseases because of the nature of their work. This study aimed to gain an understanding of job-related health risks by comparing overall health awareness, presence of physical and mental disabilities and their causes, medical use patterns, and quality of life of the general public through a survey. Methods: In this comparative study, police officer data were collected through a survey conducted from October 1, 2022, to November 15, 2022, and general public data from the 8th National Health and Nutrition Examination Survey of Korea were used for comparison. Results: Police officers' health perception of physical or mental disabilities was significantly more negative than that of the general public because of their work characteristics, patterns, and functions. In addition, police officers with disabilities had severe work and daily living limitations, and their awareness of their overall quality of life was low enough to warrant alarm. Despite their high rates of seeking treatment in medical institutions, continuous medical use was limited. Conclusion: More research on major diseases to which police officers are at risk of exposure is necessary to analyze risk factors and accumulate related data to systematize health management. In addition, Korean medicine treatment techniques with excellent disease prevention are recommended for the health management of police officers.